Strategi Bauran Pemasaran dalam Meningkatkan Penghimpunan Dana Deposito di BPRS Sarana Prima Mandiri Kantor Pusat Pamekasan - Fitria, Anisa; Umam, Khotibul (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This research is grounded in the crucial role of marketing strategy in driving the growth of mudharabah deposit funds in Islamic financial institutions. The aim of this study is to analyze the implementation of the 7P marketing mix in increasing the collection of mudharabah deposit funds at PT BPRS Sarana Prima Mandiri. The research employs a qualitative approach with a descriptive research design. Data were collected through interviews, observation, and documentation, with the Branch Head, Head of Funding, Customer Service staff, and deposit customers serving as sources of information. The results show that PT BPRS Sarana Prima Mandiri implements a marketing mix strategy through products that comply with sharia principles, a transparent profit-sharing system, both direct and indirect promotion, friendly service, a simple process, and facilities that support customer comfort. Promotional strategies through personal relationship-building (silaturahmi) and direct visits proved to be the most effective in attracting customer interest. Nevertheless, challenges remain, including competition with other financial institutions and fluctuations in profit-sharing rates. Therefore, product innovation and stronger promotional strategies are needed to sustainably increase the collection of mudharabah deposit funds.